Watch out, he's dangerous! Electrocortical indicators of selective visual attention to allegedly threatening persons. (October 2020) - Bublatzky, Florian; Guerra, Pedro; Alpers, Georg W.
Abstract: The face of a friend indicates safety, the face of a foe can indicate threat. Here, we examine the effects of verbal instructions ('beware of this person') on the perception of unknown persons. Focusing on visual attention, face identity and facial expression information is examined during instructed threat-of-shock or safety. However, shocks never occurred. Participants quickly acquired instructed threat associations, and electrocortical processing differentiated threat- from safe-identities as well as emotional and neutral facial expressions. Importantly, face encoding varied as a joint function of identity and facial expression, as revealed by pronounced N170 amplitudes to smiling threat-identities. Moreover, instructions readily reversed previously learned affective associations leading to attention allocation and memory updating as reflected by N170, EPN and P3 amplitudes toward new threat-identities displaying angry expressions. These findings demonstrate that person perception flexibly re-adjusts according to minimal information. Intriguingly, perceptual biases occur even though the anticipated aversive consequence does not occur, with implications for research on stereotyping and anxious psychopathology.